Coupling of CO2 with epoxides catalyzed by bifunctional periodic mesoporous organosilica with ionic liquid framework. Issue 12 (14th September 2022) - Khorasani, Mojtaba; Karimi, Babak; Vali, Hojatollah
Abstract : Bifunctional periodic mesoporous organosilica with ionic liquid framework (BFPMO-IL) was found to be an efficient recoverable catalyst for the direct coupling of carbon dioxide with epoxides under solvent, additive and metal-free conditions. Abstract : Despite the fact that numerous catalytic systems have already been introduced for the direct coupling of CO2 with epoxide to obtain the corresponding cyclic carbonate, the design of new systems that can catalyze this important transformation in the absence of any metal catalyst or additives under mild reaction conditions remains a challenge. Owing to the high ability of imidazolium-based ionic liquids to activate carbon dioxide, herein, a bifunctional periodic mesoporous organosilica with an ionic liquid and ethylene framework (Cl@BFPMO-IL) was used as a support for immobilizing iodide ions as a simple and efficient organocatalyst for the preparation of cyclic carbonates from carbon dioxide with various types of epoxides under solvent, additive and metal-free reaction conditions. Subsequently, the parent Cl@BFPMO-IL was fully characterized using several typical methods, such as transmission electron microscopy (TEM), thermogravimetric analysis (TGA), nitrogen adsorption–desorption, diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), elemental analysis (CHNX), low-angle powder X-ray diffraction (PXRD) and solid-state 29 Si cross-polarization magic angle spinning nuclear magnetic resonance ( 29 Si CP-MAS NMR), showing that the iodide ions were successfully immobilized in the pores using simple ion-exchange techniques. Different epoxides were converted to the related cyclic carbonate in the presence of 1 mol% catalyst and 1 MPa of CO2 at 70 °C as the best reaction conditions. Moreover, by designing several catalyst references, it was demonstrated that the co-existence of iodide ions, bridged ionic liquid, and surface silanol groups in the nanospaces of I@BFPMO-IL led to a significant improvement in catalyst activity, which is most likely through a synergistic manner. The catalyst could also be recovered and reused at least 5 times without exhibiting any noticeable loss of activity or selectivity.